Evaluation of Renoprotective Effect of Lipoic Acid and Bosentan Against Diclofenac-Induced Acute Renal Failure - Al-Hasani, Lina; Ghaith A. Jasim; Ihsan S. Rabeea (Iraqi Journal of Pharmaceutical Sciences, 2023)
Acute renal failure also known as acute kidney injury (AKI) is a complex health condition related to significant morbidity and mortality. In hospitalized patients, around 19-33 percent of AKI episodes are linked to drug induced nephrotoxicity. Although considered safe, NSAIDs such as diclofenac have gained special attention over the past few years due to the potential risk of renal injury. The direct effect of diclofenac-induced renal injury depends on targeting the mitochondria in kidney tissue, and formation of reactive oxygen species (ROS) resulting in oxidative stress. Secondly, diclofenac inhibit renal prostaglandin production, limiting renal afferent arteriole vasodilation, increasing afferent resistance; thus decreasing the glomerular capillary pressure below normal values and glomerular filtration rate will decrease resulting in AKI. Alpha-Lipoic acid (ALA) has beneficial effects in prevention or relief of symptoms of oxidative stress- related diseases, as it acts as antioxidant and anti-inflammatory micronutrient. Bosentan is a competitive antagonist with dual endothelin-1 receptors, as renal vascular ET-1 system is upregulated under many pathophysiological situations. In present study, we investigated the effect of lipoic acid and bosentan in diclofenac induced acute renal failure in male rats.We observed that diclofenac increased serum levels of urea, creatinine, malondialdehyde, KIM-1, TGFβ1 and fibronectin significantly (p>0.05) in the induction group compared to control group. While, SOD significantly (p>0.05) reduced in the induction group compared to control group. Both of lipoic acid and bosentan alone didn’t significantly protect against diclofenac induced AKI. However, the combination group showed a significant protection against AKI. Pearson correlation analysis showed a significant positive correlation between (urea and KIM-1) and between (creatinine and KIM-1) (r2=0.792 and r2=0.677 respectively). Furthermore, there was a significant positive correlation between fibronectin and urea (r2= 0.498, p>0.01) and fibronectin and creatinine (r2=0.356, p>0.05). Interestingly, KIM-1 showed a significant positive correlation with fibronectin (r2=0.536, p>0.01).ROC curve test was performed for KIM-1 and fibronectin biomarkers. The AUC for KIM-1 was 0.986 and for fibronectin was 0.829. We concluded that combination therapy of lipoic acid and bosentan showed a significant protective effect against diclofenac-induced AKI. In addition, fibronectin could be a promising biomarker for detection and diagnosis of acute kidney injury.Key words: Diclofenac, oxidative stress, alpha- lipoic acid, endothelin-1, bosentan